Réponses

2013-12-06T23:20:57+01:00
Bonsoir,

1) G = 4x² - 20x + 25 + (2x - 5)(3x + 4)
    G = 4x² - 20x + 25 + (6x² + 8x - 15x - 20)
    G = 4x² - 20x + 25 + 6x² + 8x - 15x - 20
    G = 10x² - 27x + 5

2) (4x² - 20x + 25) = (2x - 5)²

3) G = 4x² - 20x + 25 + (2x - 5)(3x + 4)
    G =(2x - 5)² + (2x - 5)(3x + 4)
    G =(2x - 5)(2x - 5) + (2x - 5)(3x + 4)
    G = (2x - 5)[(2x - 5) + (3x + 4)]
    G = (2x - 5)(2x - 5 + 3x + 4)
    G = (2x - 5)(5x - 1)
    
Exercice 37.

a) 64x² - 25 = (8x + 5)(8x - 5)
b) 36x² - 16 = 4(9x² - 4)
                   = 4(3x - 2)(3x + 2)
c) 1 - 100x² = (1 + 10x)(1 - 10x)
d) -9 + x² = x² - 9
                = (x + 3)(x - 3)
2013-12-06T23:21:20+01:00
Numéro 37: a) (8+5)(8-5) b) (6x+4)(6x-4)
c) (1+10x)(1-10x) d) (x+3)(x-3)